Day 2 Wed, October 13, 2021 2021
DOI: 10.2118/206636-ms
|View full text |Cite
|
Sign up to set email alerts
|

Control Over the Fracture in Carbonate Reservoirs as a Result of an Integrated Digital Stimulation Approach to Core Testing and Modeling

Abstract: The oilfield industry is rapidly changing towards reduced CO2 emissions and sustainability. Although hydrocarbons are expected to remain the leading source for global energy, costs to produce them may become prohibitive unless new breakthrough in technology is established. Fortunately, the digital revolution in the IT industry continues at an accelerating pace. A digital stimulation approach for tight formations is presented, using the achievements of one industry to solve the challenges of another. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Many issues, such as the placement of wells in the reservoir, the sequence of putting them into operation, maintaining reservoir pressure by pumping various working agents into the reservoir, regulation and direction of movement of reservoir fluids, are solved on the basis of the methods of underground hydraulics. The technological and economic effect of oil and gas production from hydrocarbon deposits depends on the correct solution of these issues [9][10][11]. Considering that nowadays the main technology of oil reservoirs development is connected with oil displacement by water, it is urgent to increase the efficiency of this process by using various solutions [12,13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many issues, such as the placement of wells in the reservoir, the sequence of putting them into operation, maintaining reservoir pressure by pumping various working agents into the reservoir, regulation and direction of movement of reservoir fluids, are solved on the basis of the methods of underground hydraulics. The technological and economic effect of oil and gas production from hydrocarbon deposits depends on the correct solution of these issues [9][10][11]. Considering that nowadays the main technology of oil reservoirs development is connected with oil displacement by water, it is urgent to increase the efficiency of this process by using various solutions [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…One of the most important issues in increasing the degree of oil recovery from the subsurface is the study of structural and mechanical properties of polymer solutions, their influence on the filtration process in the reservoir and ways to regulate them. At present, a large amount of theoretical and experimental material has been accumulated to study the structural and mechanical properties and flow characteristics of non-Newtonian oils [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. Studies have shown that during the development of wells that have opened deposits of heavy high-viscosity oils, there are complications associated with the difficulty of lifting oil to the surface.…”
Section: Introductionmentioning
confidence: 99%